2012
DOI: 10.1038/nsmb.2391
|View full text |Cite
|
Sign up to set email alerts
|

Association of UHRF1 with methylated H3K9 directs the maintenance of DNA methylation

Abstract: SUMMARY A fundamental challenge in mammalian biology has been elucidating mechanisms linking DNA methylation and histone post-translational modifications. Human UHRF1 (ubiquitin-like, PHD and RING finger containing 1) has multiple domains that bind chromatin and is implicated genetically in DNA methylation maintenance. However, molecular mechanisms underlying DNA methylation regulation by UHRF1 are poorly defined. Here we show that UHRF1 association with methylated histone H3 lysine 9 (H3K9) is required for DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
314
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 329 publications
(346 citation statements)
references
References 39 publications
15
314
1
3
Order By: Relevance
“…As the activity of DNMT1 is stimulated by the binding of its cofactor, NP95, to H3K9me3 (Rothbart et al 2012(Rothbart et al , 2013, SETDB1-dependent deposition of this mark may also influence the efficiency of maintenance DNA methylation. Notably, NP95 expression is down-regulated in PGCs (Kurimoto et al 2008), and the remaining protein is detected predominantly in the cytoplasm (Seisenberger et al 2012), likely compromising maintenance methylation at a global level.…”
Section: Discussionmentioning
confidence: 99%
“…As the activity of DNMT1 is stimulated by the binding of its cofactor, NP95, to H3K9me3 (Rothbart et al 2012(Rothbart et al , 2013, SETDB1-dependent deposition of this mark may also influence the efficiency of maintenance DNA methylation. Notably, NP95 expression is down-regulated in PGCs (Kurimoto et al 2008), and the remaining protein is detected predominantly in the cytoplasm (Seisenberger et al 2012), likely compromising maintenance methylation at a global level.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that knockdown of UHRF1 leads to a dramatic decrease in DNMT1 (20). Indeed, qRT-PCR and immunoblotting analyses revealed that knockdown of UPAT resulted in a drastic decrease in the levels of DNMT1 protein, but not mRNA, in HCT116 cells (Fig.…”
Section: Significancementioning
confidence: 99%
“…Genetic studies have demonstrated that UHRF1 is essential for faithful DNMT1-mediated maintenance methylation (Bostick et al 2007;Sharif et al 2007), and our laboratory determined that the DNA methylation maintenance function of UHRF1 is linked to its ability to engage di-and trimethylated H3K9 (H3K9me2/3)-transcriptionally repressive chromatin marks enriched at pericentric heterochromatin and telomeres (Ebert et al 2006;Grewal and Elgin 2007;Hawkins et al 2010;Ernst et al 2011)-through the first Tudor subdomain of its tandem Tudor domain (TTD) (Fig. 1A,B; Nady et al 2011;Rothbart et al 2012a). The adjacent PHD of UHRF1 (Fig.…”
mentioning
confidence: 99%